Financial Distress Of Companies Listed On Indonesian Stock Exchange During Covid-19 Pandemic - Diota Prameswari Vijaya; M Rudi Irwansyah; Ni Wayan Yulianita Dewi (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
The aim of the study is to examine and analyze the effect of the financial performance of companies listed on Indonesian Stock Exchange on financial distress during the Covid-19 pandemic. The financial performance used liquidity ratio, solvency ratio, profitability ratio and sales growth. The sample in this study are trade, services and investment sector of listed companies in 2020 and 2021 that are 158 companies. The results of this study showed that the company’s performance had a simultaneous effect on the company’s financial distress and the profitability ratio had a negative and significant effect on financial distress. Meanwhile, the liquidity ratio, solvency ratio and sales growth have no significant effect on financial distress. Keywords: liquidity ratio, solvency ratio, profitability ratio, sales growth, financial distress